Jenis Sekolah dan Religiusitas - Kartika Dian Nova; Hepi Wahyuningsih (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2004)
The current study is aimed at testing whether a difference in Religiosity exist between students in Integrated Islamic Elementary School (SDIT) and State Elementaray School (SDN). The hypothesis of this study was that there is a difference in religiosity between SDIT and SDN students. It is expected that SDIT students show higher religiosity. Subjects of this study were 30 students from one SDN in Northern Yogyakarta and 30 students from SDIT in Eastern and Northern Yogyakarta. All subjects were Muslims, with age range between 11 to 13 years. A Likert Religiousity scale which consists of cognitive dimension as well as belief, ritual, experience and consequential dimension is used to asess students religiousity. Data were analysed using T- test. The results show that there is a difference in religiousity between SDIT and SDN students exist with t = 4.006 and p=0000. Thus, the hypothesis of this study is supported by the finding. Practical and theoretical implications are discussed.Key Words: Religiousity, Type of School